PENINGKATAN KEAKTIFAN BELAJARDAN KETERAMPILAN MENULISTEMA WE LOVE WHAT WE DO MELALUI MODEL WHO AM I QUIZ PADA SISWA KELAS VIIH SMP NEGERI 1 TALANG SEMESTER GENAP TAHUN PELAJARAN 2019/2020 - Uyub, Moh.; Suriswo; Basukiyatno (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2021)
The Who Am I Quiz Learning Model is a learning model designed in such a way as to increase student learning activity and have implications for increasing writing skills. The purpose of this study was to improve student learning activeness and writing skills of class students. To strengthen and facilitate this study the authors used several accurate references. This study used two stages, namely cycle I and cycle II. Each cycle consists of planning, acting, observing, and reflecting. From the results of the study, the percentage value of student learning activeness in the first cycle was 56.25% in the active category and very active and increased in the second cycle, namely 93.63% in the active and very active category. While the average value of writing skills in cycle I was 66% and increased in cycle II to 76.3. Meanwhile, the percentage of completeness in the first cycle was 62.5% and increased in the second cycle to 93.75%. This improvement proves the success of descriptive text learning through the Who Am I Quiz learning model.